2018
DOI: 10.3389/fphar.2018.01375
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula stoechas (L) a Very Potent Antioxidant Attenuates Dementia in Scopolamine Induced Memory Deficit Mice

Abstract: The objective of the current project was to explore the pharmacotherapeutic role of Lavandula stoechas (L) for the management of dementia. Dementia is considered a global challenge of current century seeking special attention of pharmacologists to explore its best remedies. Methanolic extract of aerial parts of L. stoechas was tested for phytochemical analysis along with free radical scavenging activity. Behavioral studies were performed on scopolamine induced amnesic mice by using elevated plus maze (EPM), li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…Supporting evidence suggested that lavender oil (Lavandula stoechas L.) is a very potent antioxidant attenuating dementia in Sco-induced memory deficit in mice brains. The authors also demonstrated that the methanolic extract of L. stoechas reduced brain AChE and MDA levels while improved SOD, CAT, and GSH levels [36]. Additionally, our group reported that the lavender essential oils from L. angustifolia ssp.…”
Section: Effects Of the Essential Oil MIX On Brain Oxidative Status Imentioning
confidence: 80%
“…Supporting evidence suggested that lavender oil (Lavandula stoechas L.) is a very potent antioxidant attenuating dementia in Sco-induced memory deficit in mice brains. The authors also demonstrated that the methanolic extract of L. stoechas reduced brain AChE and MDA levels while improved SOD, CAT, and GSH levels [36]. Additionally, our group reported that the lavender essential oils from L. angustifolia ssp.…”
Section: Effects Of the Essential Oil MIX On Brain Oxidative Status Imentioning
confidence: 80%
“…The specimen was preserved in the herbarium of the GCU and was assigned a voucher number: GC.Herb.Bot.3386. The extraction was conducted in methanol, by using simple maceration, as described in our previous study [ 15 ]. Then, fractional extraction was conducted by using different solvents, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical studies were performed to assess the level of acetylcholinesterase (AChE), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) in the brain homogenates of mice, of all groups, using standard protocols. Detailed procedures of these tests are described in a previously published paper in this series [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations